2017
DOI: 10.1152/physiolgenomics.00050.2017
|View full text |Cite
|
Sign up to set email alerts
|

Systems genetics identifies a co-regulated module of liver microRNAs associated with plasma LDL cholesterol in murine diet-induced dyslipidemia

Abstract: Chronically altered levels of circulating lipids, termed dyslipidemia, is a significant risk factor for a number of metabolic and cardiovascular morbidities. MicroRNAs (miRNAs) have emerged as important regulators of lipid balance, have been implicated in dyslipidemia, and have been proposed as candidate therapeutic targets in lipid-related disorders including atherosclerosis. A major limitation of most murine studies of miRNAs in lipid metabolic disorders is that they have been performed in just one (or very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…We have previously reported that diet significantly affects miRNA and mRNA expression in the DO population ( Coffey et al 2017 ). Moreover, having identified relationships between expression and genetic architecture, we sought to explore the effect of diet by comparing the cis and trans architecture of eQTL from separate genome scans of HFCA-fed mice ( n = 134) and HP-fed mice ( n = 114).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported that diet significantly affects miRNA and mRNA expression in the DO population ( Coffey et al 2017 ). Moreover, having identified relationships between expression and genetic architecture, we sought to explore the effect of diet by comparing the cis and trans architecture of eQTL from separate genome scans of HFCA-fed mice ( n = 134) and HP-fed mice ( n = 114).…”
Section: Resultsmentioning
confidence: 99%
“…Given our previous reports of diet effects on hepatic gene expression ( Coffey et al 2017 , 2019 ) and our observation of differing correlative structures between homologous GWAS candidate genes and traits in the DO population, we hypothesized that diet could affect the overall structure of eQTL and mirQTL. Thus, we performed eQTL and mirQTL analysis with diet as an interactive covariate and identified 6155 significant eQTL and 23 mirQTL (Figure S6, A and B), after completing individual permutation thresholds ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The third experiment examined the effect of dietary cholesterol on Enho expression in liver of mice from DO mouse population developed from eight inbred strains of mice [31] . Full details on animal handling, feeding, measurement of phenotypes, and microarray analysis were previously published [32] , [33] . Briefly, a cohort of 288 DO mice were fed either an atherogenic high-fat, high-cholesterol diet with cholic acid (HFCA, n = 144) or a calorie-matched non-atherogenic high protein (HP, n = 144) diet for 18 wk.…”
Section: Methodsmentioning
confidence: 99%